Assessment of freezing and thawing cycle (FTC) effects on mixed mode I/III fracture toughness and work of fracture of HMA asphalt mixtures. (April 2022) - Haghighatpour, Pegah Jafari; Aliha, M.R.M.
Highlights: Effect of freeze/thaw cycles (FTC) on mixed mode I/III fracture of asphalt concrete. Reduction of both fracture toughness and work of fracture by increasing the FTC numbers. Observing plateau form curve after 7th Freeze/thaw cycle. Reducing the fracture toughness by moving from pure modes towards pure mode II. Increasing the work of fracture by decreasing the mode mixity. Conducting low temperature fracture experiments using ENDB specimen. Abstract: Asphalt fracture due to initiation and propagation of cracks is a major failure mode especially at cold regions. Freezing and thawing phenomenon that is often seen at rainy environments can double the damage of overlays and pavement systems. Study of the crack resistance of asphalt concrete materials exposed to such environmental condition can provide good insights for the designers and engineers of pavement structures. Mixed mode I/III (combined opening-tearing mode) is a possible mode of fracture in overlays especially for edge cracks located in road bends. The effects of freeze/thaw mechanism on mixed mode I/III fracture characteristics of asphalt mixtures have not been studied till now. Hence, in this research using Edge Notch Disc Bend (ENDB) test configuration a series of mixed mode I/III fracture experiments are conducted on fixed hot mix asphalt (HMA) mixture exposed to different numbers of freeze/thaw cycles (FTCs). Each FTC cycle was consist of thawing inside the water at 25 °C for 12 h and then storing the ENDB sample inside a freezer at −25 °C for 12 h. The fracture experiments were done after exposing five FTCs of 1, 3, 5, 7 and 9 and the corresponding values of fracture toughness and work of fracture obtained from different cycles were compared with the fracture results of control HMA mixture (i.e. with no freeze/thaw cycles). The results showed that in general both fracture toughness and fracture energy values are reduced by increasing the number of FTCs showing the negative influence of freezing and thawing mechanism on the low temperature cracking resistance of HMA mixtures. However, the rate of cracking resistance reduction becomes smaller by increasing the number of FTCs and typically after applying seven freeze/thaw cycles a plateau form is seen for the curves of fracture toughness and work of fracture. Such endurance limit range that is approximately 0.4 times the corresponding fracture strength of the control HMA mixture can be used as a design input parameter for estimating the long term performance of pavements subjected to both traffic loads and freeze/thaw cycles in real situations.